2005
DOI: 10.1182/blood-2004-12-4608
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of proteins involved in iron metabolism in hepcidin-deficient mice

Abstract: Evidence is accumulating that hepcidin, a liver regulatory peptide, could be the common pathogenetic denominator of all forms of iron overload syndromes including HFE-related hemochromatosis, the most prevalent genetic disorder characterized by inappropriate iron absorption. To understand the mechanisms whereby hepcidin controls iron homeostasis in vivo, we have analyzed the level of iron-related proteins by Western blot and immunohistochemistry in hepcidin-deficient mice, a mouse model of severe hemochromatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
87
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 22 publications
13
87
2
2
Order By: Relevance
“…Hepcidin negatively controls the plasma iron pool, by binding and internalizing the iron exporter ferroportin on cells that release iron to the circulation, as duodenal enterocytes, macrophages and hepatocytes (Donovan, et al, 2005;Nemeth, et al, 2004). Consistently, hepcidindeficient mice (Nicolas, et al, 2001;Viatte, et al, 2005) and humans with hepcidin mutations (Roetto, et al, 2003) develop severe iron overload. Conversely, mice with increased transgenic expression of hepcidin in the liver manifest severe iron deficiency anemia (Nicolas, et al, 2002).…”
Section: Introductionmentioning
confidence: 83%
“…Hepcidin negatively controls the plasma iron pool, by binding and internalizing the iron exporter ferroportin on cells that release iron to the circulation, as duodenal enterocytes, macrophages and hepatocytes (Donovan, et al, 2005;Nemeth, et al, 2004). Consistently, hepcidindeficient mice (Nicolas, et al, 2001;Viatte, et al, 2005) and humans with hepcidin mutations (Roetto, et al, 2003) develop severe iron overload. Conversely, mice with increased transgenic expression of hepcidin in the liver manifest severe iron deficiency anemia (Nicolas, et al, 2002).…”
Section: Introductionmentioning
confidence: 83%
“…The reduction in ferroportin and its ability to export iron probably contributes to the MPTP-induced accumulation of iron observed in previous MPTP studies. Given that ferroportin is intricately regulated by hepcidin (27), the stabilization of HIF␣ by DHB, even in the presence of MPTP, could promote iron export and prevent neurodegeneration associated with MPTP. Similar to previous studies, divalent metal transporter-1 was observed to be up-regulated by MPTP (59) and this increase was sustained even in the presence of DHB (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of cytosolic HIF␣, hepcidin is down-regulated and prevented from binding to and internalizing FPT (26,27), thereby increasing the levels of the iron exporter. MPTP treatment alone was observed to result in a decrease of ferroportin levels within the SN (Fig.…”
Section: Phd Inhibition By Dhb Prevents Mptp-induced Losses In Sn Levmentioning
confidence: 99%
“…Knockouts of hepcidin in mice produce a model of hereditary hemochromatosis with severe multiorgan iron overload (6). Conversely, transgenic mice that overexpress hepcidin die at birth as a result of a severe iron deficiency anemia (7).…”
Section: Biologic Actions Of Hepcidinmentioning
confidence: 99%